While Beauty slept [large type] - Blackwell, Elizabeth Canning (Thorndike Press large print basic series., 2014)
When she hears her great-granddaughter recount a tale about a beautiful princess awakened by a handsome prince, it pushes open a door to the past, a door Elise Dalriss has long kept locked. For Elise was the companion to the real princess who slumbered -- and she is the only one left who knows the truth of what happened so many years ago. As the memories start to unfold, Elise is plunged back in to the magnificent world behind the opulent palace walls. Fleeing a hardscrabble existence and personal tragedy, she builds a new life for herself as a servant to the royal family and quickly rises within the castle hierarchy. As Elise proves herself a loyal confidante, she is drawn into the lives of an extraordinary cast of women: a beautiful queen who wakes each morning with tears on her pillow, an elderly spinster who in heartache shuts herself away, a princess who yearns to be free, and the ambitious and frightening sister who cannot accept the fact that she will never rule. Elise has guarded their secrets -- and her own -- for a lifetime.